2012
DOI: 10.1111/j.1468-2885.2012.01413.x
|View full text |Cite
|
Sign up to set email alerts
|

Fleeting, Fading, or Far-Reaching? A Knowledge-Based Model of the Persistence of Framing Effects

Abstract: The social relevance of framing effects hinges upon their ability to persist. This article develops a theoretical account of the conditions under which framing effects should vanish quickly, fade slowly, or cause permanent changes. It argues that the cognitive processes involved in mediating frame effect need to leave durable traces in a person's knowledge to raise a persistent effect. This paper distinguishes temporary changes in the accessibility of knowledge from durable changes in the applicability structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
50
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 47 publications
2
50
0
Order By: Relevance
“…Extant research in psychology reports that repeated exposure to framing, as well as making participants aware of the framing effect, does not eliminate it-and may even increase it (Levin et al 1986;Levin, Jasper, and Gaeth 1996;LeBoeuf and Shafir 2003;Chong and Druckman 2007;Druckman, Fein, and Leeper 2012;Baden and Lecheler 2012;Lecheler and de Vreese 2011). This is presumably because repeated consideration increases focus on the aspects highlighted by the frame (Chong and Druckman 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Extant research in psychology reports that repeated exposure to framing, as well as making participants aware of the framing effect, does not eliminate it-and may even increase it (Levin et al 1986;Levin, Jasper, and Gaeth 1996;LeBoeuf and Shafir 2003;Chong and Druckman 2007;Druckman, Fein, and Leeper 2012;Baden and Lecheler 2012;Lecheler and de Vreese 2011). This is presumably because repeated consideration increases focus on the aspects highlighted by the frame (Chong and Druckman 2007).…”
Section: Resultsmentioning
confidence: 99%
“…the magnitude of the change in political opinions after each exposure) and its (2) duration (i.e. how long this change lasts; Baden & Lecheler, 2012;Zaller, 1992). Whereas these dimensions are likely positively correlated, there is evidence that strong effects can dissipate quickly (Druckman & Nelson, 2003) and that small effects may last over longer periods of time (Lecheler & De Vreese, 2013).…”
Section: Repetitive News Framing 341mentioning
confidence: 94%
“…Interestingly, this learning process also heightens the chance of agreeing with a frame's advocated standpoints (e.g. Baden & Lecheler, 2012;Slothuus, 2008). 1 Research in persuasion has shown that repetition indeed leads to increased agreement with a persuasive message, specifically if repetitions are spaced over longer periods of time (Cacioppo & Petty, 1979;Fernandes, 2013;Gorn & Goldberg, 1980;Stephens & Rains, 2011).…”
Section: Repetitive News Framing 341mentioning
confidence: 96%
See 1 more Smart Citation
“…Indeed, the question of whether the learning effects shown in this study lead to actual long-term storage and incorporation into existing schemata must be a topic for future research. Future studies could introduce longitudinal experimental designs, where the repetitive or competitive consumption of news is tracked over time (Baden & Lecheler, 2012). However, we want to note that experimental designs such as ours are commonly used, and have allowed us to disentangle the psychological processes that lead to news learning.…”
mentioning
confidence: 99%